Prevalence and Factors Associated with Occupational Musculoskeletal Disorders among the Nurses of a Tertiary Care Center of Nepal (International Journal of Occupational Safety and Health, 2023)
Introduction: Musculoskeletal disorders (MSDs) are injuries or pain in the human musculoskeletal system which could lead to temporary or permanent impairments. The nature of nursing jobs makes nurses vulnerable to MSDs. This study aimed to assess the prevalence and potential risk factors associated with MSDs among nurses.Methods: In between March to June 2021, a cross-sectional study was conducted among 165 nurses using self-administered questionnaires. A standardized Nordic Questionnaire was used to measure MSDs. Pearson’s chi-square test and binary logistic regression at a 5% level of significance were performed to identify factors associated with upper extremities and spinal musculoskeletal disorders (UMSD) and lower extremities musculoskeletal disorders (LMSD). Variables associated with UMSD and LMSD in bivariate analysis were subjected to multiple logistic regression. Results: The prevalence of UMSD and LMSD experienced by nurses was 86.1% (95% CI: 79.4%-90.9%) and 66.1% (95% CI: 58.9%-74.3%), respectively. Among several factors, working in same position for long periods (AOR: 4.16, 95% CI: 1.2-13.4), not receiving training in injury prevention programs (AOR: 3.15, 95% CI: 1.0-9.2), not enough rest breaks during the day (AOR: 4.65, 95% CI: 1.3-15.9) and moderate to higher job stress (AOR: 3.62, 95% CI: 1.2-10.8) were found to be significantly associated with UMSD. Not having enough rest breaks during the day (AOR: 2.19, 95% CI: 1.0-4.7) was significantly associated with LMSD.Conclusion: Higher prevalence of MSDs among nurses is a serious concern that threatens individual health as well as the overall healthcare system. Sensitization and capacity enhancement programs on the issue could prevent MSDs among nurses.